2014
DOI: 10.3310/hsdr02530
|View full text |Cite
|
Sign up to set email alerts
|

A rapid synthesis of the evidence on interventions supporting self-management for people with long-term conditions: PRISMS – Practical systematic RevIew of Self-Management Support for long-term conditions

Abstract: BackgroundDespite robust evidence concerning self-management for some long-term conditions (LTCs), others lack research explicitly on self-management and, consequently, some patient groups may be overlooked.AimTo undertake a rapid, systematic overview of the evidence on self-management support for LTCs to inform health-care commissioners and providers about what works, for whom, and in what contexts.MethodsSelf-management is ‘the tasks . . . individuals must undertake to live with one or more chronic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
451
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(479 citation statements)
references
References 240 publications
(1,371 reference statements)
12
451
1
3
Order By: Relevance
“…39 The findings of the current study concur with much of this earlier work. Taylor and colleagues 40 rapid synthesis of self-management support for all long-term conditions explored what works, for whom, and in what contexts. They identified a need for a culture of actively supporting self-management as a normal, expected aspect of the provision of care; the need for tailoring to the individual, their culture and beliefs, and the time point in the condition; the need for good communication between patient and HCP; information and education; support with psychological impact of long-term conditions; and implementing a whole-systems approach to self-management support.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…39 The findings of the current study concur with much of this earlier work. Taylor and colleagues 40 rapid synthesis of self-management support for all long-term conditions explored what works, for whom, and in what contexts. They identified a need for a culture of actively supporting self-management as a normal, expected aspect of the provision of care; the need for tailoring to the individual, their culture and beliefs, and the time point in the condition; the need for good communication between patient and HCP; information and education; support with psychological impact of long-term conditions; and implementing a whole-systems approach to self-management support.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Indeed, our findings provide further evidence for the limitations of 7 a 'one size fits all' approach to self-management support [10,40,41], and demonstrate the need for tailoring the 8 design, content and delivery of self-management interventions to the needs and preferences of specific groups of 9 cancer survivors in order to optimise their 'reach'. Firstly, although participants' views on the value of sharing 10 their experiences with fellow cancer survivors lends further support to the benefits of peer support in this cohort 11 [42,43], perceived similarity with others (e.g., in terms of age or time since diagnosis) was a key influence on the 12 acceptability of group-based interventions.…”
mentioning
confidence: 99%
“…Systematic reviews on psychological interventions for asthma found that these methods may be effective, but were inconclusive due to small sample sizes and differing outcome measures (see Smith & Jones, 2015;Yorke et al, 2007). Future studies on interventions should more explicitly incorporate efficacy building and longitudinally measure changes in self-efficacy to further support the importance of self-efficacy for people with asthma, PTSD, and co-morbid disorders (Battersby et al, 2010;Marks et al, 2005;Taylor et al, 2014).…”
Section: Regression Analyses Of Locus Of Control and Self-efficacymentioning
confidence: 99%
“…A central aspect of self-management in chronic illness is 'perceived control'. Decreased perceived control is common in people with asthma and is associated 5 with health outcomes (Adams et al, 2004), and both Marks et al (2005) and Taylor et al (2014) suggest an important aim of self-management of chronic illness is to enhance the agency/control construct 'self-efficacy'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation